1999
DOI: 10.1161/01.str.30.9.1962
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Delayed Cell Injury After Transient Global Ischemia in Mutant Mice With CuZn Superoxide Dismutase Deficiency

Abstract: Background and Purpose-We have demonstrated that copper-zinc superoxide dismutase (CuZn-SOD), a cytosolic isoenzyme of SODs, has a protective role in the pathogenesis of superoxide radical-mediated brain injury. Using mice bearing a disruption of the CuZn-SOD gene (Sod1), the present study was designed to clarify the role of superoxide anion in the pathogenesis of selective vulnerability after transient global ischemia. Methods-Sod1 knockout homozygous mutant mice (Sod1 Ϫ/Ϫ) with a complete absence of endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 36 publications
1
82
1
1
Order By: Relevance
“…Using either mice or rats overexpressing SOD1 or SOD1-knockout mice, it has been shown that SOD1 reduces brain injury after transient global ischemia (Chan et al, 1998;Kawase et al, 1999;Murakami et al, 1997). While most studies focused on hippocampal injury, one study using male transgenic rats, found neuroprotection in caudoputamen similar to the results of our study (Chan et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…Using either mice or rats overexpressing SOD1 or SOD1-knockout mice, it has been shown that SOD1 reduces brain injury after transient global ischemia (Chan et al, 1998;Kawase et al, 1999;Murakami et al, 1997). While most studies focused on hippocampal injury, one study using male transgenic rats, found neuroprotection in caudoputamen similar to the results of our study (Chan et al, 1998).…”
Section: Discussionsupporting
confidence: 79%
“…Together, with the downstream enzymes catalase and glutathione peroxidase (which convert H 2 O 2 to water and oxygen), SOD1 reduces cellular free radicals. This function is important, because mice lacking the SOD1 gene develop numerous abnormalities, including reduced fertility (17), motor axonopathy (18), increased age-associated loss of cochlear hair cells (19) and neuromuscular junction synapses (20), and enhanced susceptibility to a variety of noxious assaults on the nervous system, such as axonal injury (21), ischemia (22,23), hemolysate exposure (24), and irradiation (25).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…In mice, expression of mutant SOD1, but not complete elimination of SOD1, causes ALS. Nonetheless, SOD1 -knockout mice show reduced fertility (Matzuk et al ., 1998), motor axonopathy (Shefner et al ., 1999), age-associated loss of cochlear hair cells (McFadden et al ., 2001) and neuromuscular junction synapses , as well as enhanced susceptibility to a variety of noxious assaults on the nervous system, such as axonal injury (Reaume et al ., 1996), ischaemia (Kondo et al ., 1997;Kawase et al ., 1999), haemolysate exposure (Matz et al ., 2000) and irradiation (Behndig et al ., 2001). Given the toxicity of the mutant protein and the functional importance of the wild-type, the ideal therapy for ALS would selectively block expression of the mutant while retaining expression of wild-type protein.…”
Section: Introductionmentioning
confidence: 99%